2020
DOI: 10.1101/2020.06.04.133959
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Experiences of cervical cancer survivors in Chitwan, Nepal: a qualitative study

Abstract: 15 Introduction 16 Cervical cancer is a global leading cause of morbidity and mortality. The majority of cervical 17 cancer deaths occur in developing countries including Nepal. Though knowledge of cervical 18 cancer is an important determinant of women's participation in prevention and screening for 19 cervical cancer, little is known about this topic in Nepal. This study explores the experiences of 20 cervical cancer survivors and assesses the attitude of family and community towards it and 21 stigma related… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…In Asian countries including Cambodia, there is a strong hesitation to publically talk about sexual and reproductive health, and education regarding sexual and reproductive health can be difficult (10,(23)(24)(25). This may relate to the fact that the most common source of information on cervical cancer was family and friends.…”
Section: Table 2 Number and Proportion Of Women Who Reported Ever Und...mentioning
confidence: 99%
See 2 more Smart Citations
“…In Asian countries including Cambodia, there is a strong hesitation to publically talk about sexual and reproductive health, and education regarding sexual and reproductive health can be difficult (10,(23)(24)(25). This may relate to the fact that the most common source of information on cervical cancer was family and friends.…”
Section: Table 2 Number and Proportion Of Women Who Reported Ever Und...mentioning
confidence: 99%
“…On the other hand, it also suggests that correct knowledge does not necessarily lead directly to correct behavior. One of the barriers is that the concept and practice of prevention are not widely recognized in society, and people do not consider it necessary to visit health facilities unless they have serious symptoms (23,25,28). Some people do not want to be identified as having cervical cancer by screening for fear that having cervical cancer will lead to social stigma and interfere with their daily lives due to discrimination and prejudice in the community (23).…”
Section: Table 2 Number and Proportion Of Women Who Reported Ever Und...mentioning
confidence: 99%
See 1 more Smart Citation
“…In all, 49 studies reported the impact of a woman's diagnosis of cervical cancer on social support 13–61 . Social support was most commonly reported through the European Organization for Research and Treatment of Cancer Core Quality of Life questionnaire (EORTC) tool using the categorization of social functioning ( n = 18) 17,19,23,26–28,30,33,34,44,45,48,51,55,57,59 .…”
Section: Resultsmentioning
confidence: 99%
“…For example, in South Africa, a woman reported that she continued to ask her partner for sex out of fear that he would have sex with another woman if she did not offer it 40 . However, it should be noted that several studies did report positive responses with regard to social support and their diagnosis of cervical cancer 15,24,40,41,52 . For example, a woman in Ghana reported that not only did her spouse help take care of her, but her children assisted with her care as well 15 …”
Section: Resultsmentioning
confidence: 99%